AWARENESS AND ATTITUDE TOWARDS STROKE AND ITS PREVENTION AMONG HYPERTENSIVE AND NON-HYPERTENSIVE PEOPLE - K p, Sreejesh; K s, Athira; Green M J, Heydey (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: objectives of the study are to compare the awareness and and attitude towards stroke and its prevention among hypertensives and non-hypertensives and compare the awareness and attitude towards stroke and its prevention among hypertensives and Non-hypertensives (2) to find out the association between the awareness and attitude toward stroke and its prevention with selected demographic variables among hypertensives and non -hypertensives. Methods: Descriptive survey design was adopted for the study. Convenience sample technique was used to select 70 hypertensive and 70 non-hypertensive people at 1st and 2nd ward of Nayarambalam Panchayat, Ernakulam, Kerala. The data collection tool consists of a structured questionnaire to identify demographic data and awareness about stroke and prevention and five-point Likert scale to assess attitude toward stroke and its prevention. The datum was analyzed using descriptive and inferential statistics. Results: Even though the mean awareness score of non hypertensives (11.9714) was relatively higher than the hypertensives (11.6286) there was no significant difference between them. Similarly, mean attitude score of hypertensive people (32.0286) was relatively higher than the non-hypertensive people (30.929) there was no significant difference between. There was significant association found between educational level of non-hypertensive people and awareness regarding stroke and its prevention and educational level of hypertensive people and attitude toward stroke and its prevention. Conclusion: In conclusion of this study result shows that awareness regarding stroke and its prevention was average even among hypertensives so intense educational need for high-risk group.